Investigate the Relationship between Leverage Deviations of Management Remuneration and Corporate Financial Supply Chain Management on Investment Diversions Accepted By Tehran Stock Exchange - Seyyed Hesamedin Hedayat Zadeh (International Journal of Supply Chain Management, 2019)
Abstract This study examines the relationship between financial leverage deviations and supply chain management rewards on investment diversions in companies admitted to Tehran Stock Exchange during the period of 1387-1395. Therefore, information and statistics of 70 Tehran Stock Exchange members were analyzed using panel data approach and tested by hypothesis testing of three models. The results of this research show that there is a greater gap in the remuneration leverage of the management and the company, which leads to further gaps in investment diversions. The difference between the remuneration leverage and the company's leverage is also a negative relationship with the firm's firm's investment intensity. Ultimately, when the remuneration levy is lower than (more than) the company's financial leverage, it is likely that much investment will increase the value of equity and the value of debt reduces.